2006
DOI: 10.1080/08037050600963040
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of insomnia in patients with essential hypertension

Abstract: Our results showed that insomnia is common in patients with essential hypertension and indicate an association between insomnia and gender, known duration of hypertension and number of hypertensive drugs taken. Untreated essential hypertension insomniacs were characterized by less pronounced nocturnal fall in both systolic and diastolic blood pressure compared with non-insomniacs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
25
1
3

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 15 publications
2
25
1
3
Order By: Relevance
“…There are only limited studies available to compare the rate of insomnia in patients with hypertension with that of our data. 19,20 In this study, the prevalence of insomnia among hypertensive population was found to be 47.2%. This observation corroborated with the prevalence reported in a European population.…”
Section: Discussionmentioning
confidence: 53%
See 2 more Smart Citations
“…There are only limited studies available to compare the rate of insomnia in patients with hypertension with that of our data. 19,20 In this study, the prevalence of insomnia among hypertensive population was found to be 47.2%. This observation corroborated with the prevalence reported in a European population.…”
Section: Discussionmentioning
confidence: 53%
“…This observation corroborated with the prevalence reported in a European population. 20 However, in another study (POL-MONICA BIS) in Warsaw metropolitan population, prevalence of insomnia was found to be low (30.7%). 19 Nevertheless, it should be noted that the prevalence of insomnia reported in this study among patients who reached out to physicians for the management of hypertension was higher than reported in general Indian population, indicating the lack of relevance given by healthcare professionals towards the condition.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Recordings contain 21 EEG channels from the 10-20 system plus A1/A2 references, two EOG channels (EOGL and EOGR), breathing, EMG and ECG; with sampling frequency 128 Hz. These datasets come from several different projects, including studies of effect of diazepam and midazolam (Durka et al 2002), hypertension (Prejbisz et al 2006), insomnia Niemcewicz 2000, 2001;Niemcewicz et al 2001) and clinical depression (Dróżdż et al 2007;Radziwoń-Zaleska et al 2006), both from control and from target groups.…”
Section: Experimental Datamentioning
confidence: 99%
“…1-4 Indeed, a great many of hypertensive patients suffer additional distress because of poorer quality sleep, 5-7 and the degree of poor sleep quality is associated with the severity of the hypertension. [7][8][9][10] These observations suggest the possibility that hypertension and the disrupted sleep might share a common etiology, namely adrenergic overdrive. However, the pathophysiology behind sleep disturbance related to essential hypertension is much less well understood.…”
mentioning
confidence: 93%